2013
DOI: 10.6066/jtip.2013.24.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Hydroxypropylated and Crosslinked Arrowroot Starch

Abstract: Dual-modified arrowroot starch using hydroxypropylation and cross-linking methods was carried out to overcome the deficiency in of native arrowroot starches for food processing application. The modification applied the combination concentration of propylene oxide (8, 10, and 12%) and ratio of sodium trimetaphosphate (STMP):sodium tripolyphosphate (STPP) (1%:4%, 2%:5%, and 3%:6%). The resulting dual-modified arrowroot starches had lower gelatinization temperature (68.45-70.00ºC) than that of native arrowroot st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
2
0
3
Order By: Relevance
“…MOCAF samples mixed with citrate buffer solution pH 3 had the highest peak viscosity value, and MOCAF samples mixed with citrate buffer solution pH 7 had the lowest peak viscosity values. The results of previous studies showed that the peak viscosity of arrowroot starch modified with 10% propylene oxide was higher at pH 3.5 than at pH 6.5 (Rahaju Maulani et al, 2013). In addition, amylopectin levels are responsible for the granule development process (Putri, 2015).…”
Section: Peak Viscosity (Pv)mentioning
confidence: 97%
“…MOCAF samples mixed with citrate buffer solution pH 3 had the highest peak viscosity value, and MOCAF samples mixed with citrate buffer solution pH 7 had the lowest peak viscosity values. The results of previous studies showed that the peak viscosity of arrowroot starch modified with 10% propylene oxide was higher at pH 3.5 than at pH 6.5 (Rahaju Maulani et al, 2013). In addition, amylopectin levels are responsible for the granule development process (Putri, 2015).…”
Section: Peak Viscosity (Pv)mentioning
confidence: 97%
“…Vulnerabilities of starch include sensitivity to processing conditions such as stirring, acidic environments, high temperatures, unstable viscosity, and low solubility [1,[6][7][8][9].…”
Section: Natural Starch Presents Limitationsmentioning
confidence: 99%
“…Penelitian dilakukan di Laboratorium Program Studi Teknologi Pangan UPN "Veteran" Jawa Timur, Laboratorium Gizi Universitas Airlangga, Laboratorium FMIPA Universitas Negeri Malang serta Laboratorium Departemen Ilmu dan Teknologi Pangan IPB. Parameter yang diamati meliputi warna (Kaemba et al, 2017), kadar kalsium (AOAC, 2005), kadar amilosa (Andarwulan et al, 2011), swelling power (Kaur et al, 2011), freeze thaw stability (Rahaju et al, 2013), serta uji perlakuan terbaik menggunakan SEM (Scanning Electron Microscope) dan RVA (Rapid Visco Analyzer).…”
Section: Metode Pelaksanaanunclassified
“…Terhambatnya rekristalisasi menyebabkan penurunan nilai sineresis. Nilai sineresis yang rendah dapat digunakan sebagai indikator bahwa pati tersebut relatif stabil pada suhu rendah ( Rahaju et al, 2013).…”
Section: Freeze Thaw Stabilityunclassified
See 1 more Smart Citation